The Factors Which Influence the Quality of Education in Undeveloped Area (Multi-Cases Study in 10 Districts in Indonesia) - Widodo, Bambang Sigit (Proceeding of International Conference on Teacher Training and Education, 2016)
This study aims to find out the factors that affect the quality of education in undeveloped areas. The variables of this study were: 1) the quality of teachers, 2) the educational devices and infrastructures, 3) the community participation in education, 4) the educational funding, 5) the public perception of education, 6) the accessibility of education, 7) the educational service, and 8) the educational equity. The design of this study was quantitative with survey and multi-cases approach. The populations of this study were the communities in 10 undeveloped districts and its samples were 500 respondents. The data were collected by using questionnaires and analyzed by cluster analysis. The results show that the variables consisting of the public perception on education, the community participation, the educational funding, and educational service have score below average total score of public perception on educational equity, because Z score is minus (-). Therefore, these variables are important to be concerned in improving the quality of education. While, the quality of teachers, educational devices and infrastructures, and the accessibility of education become the variables which need to be concerned because Z score is positive (+) but it is very small. The educational equity is good because Z score is positive (+) and it is more than 1 or 1.09776. The clusters of this study are Empat Lawang and South Nias districts. The second clusters show that all variables have positive Z score with almost of Z scores are more than 1. Those variables are educational perception, quality of teachers, educational devices and infrastructures, the community participation, educational funding, educational service, accessibility of education, and educational equity. The two districts under the cluster are South Kayong and Seluma.